IMPLEMENTASI MODEL DYNAMIC PRICING KHUSUS PRODUK AGRO PERISHABLE DENGAN MEMPERTIMBANGKAN PENURUNAN KUALITAS, TINGKAT PERMINTAAN SERTA PREFERENSI PEMBELI - Fachrian, Zuhad Achmad; Asmara, Rengga; Basofi, Arif; Saputra, Ferry Astika (Jurnal Sistem Informasi, Teknologi Informatika dan Komputer, 2022)
A pricing strategy is adjusting the price of a product based on the quality of the product. Based on this, the pricing strategy used for one product may not be compatible with other products. This pricing strategy then manifests itself in the pricing policy of the company. In this study, the determination of pricing policy implies an examination of the problems with perishable products. This perishable pricing method has to deal with several unique characteristic effects based on perishables. In addition to the price factor,  demand is also determined by the quality of the product being sold. The challenge for retailers is to choose the right price that is comparable to leveraging product-based quality, triggering consumer desire to buy and unleashing demand, ultimately leading to a surge. business profits. In this study, examples of forwarding pricing are developed and then applied to regular, high-low, daily, private, and hybrid pricing policies. Performance based on each of these guidelines is evaluated under the price-conscious consumer category and the quality-conscious consumer category. Mathematical calculations are performed to determine the policy that will provide the most benefit to the price-conscious consumer category and the policy that will provide the most benefit to the quality-conscious consumer category. Price sensitivity and consumer sensitivity tests are performed to determine policy performance and the reality that arises from policy implementation.   Keywords: dynamic pricing, agro, perishables, dynamic, pricing.